Comparative Effect of 22 Dietary Sources of Fiber on Gut Microbiota of Healthy Humans in vitro - Calatayud, Marta; Van den Abbeele, Pieter; Ghyselinck, Jonas; Marzorati, Massimo; Rohs, Eric; Birkett, Anne (Frontiers in Nutrition, 2021)
Human gut microbiota has a fundamental role in human health, and diet is one of the most relevant factors modulating the gut microbial ecosystem. Fiber, fat, proteins and micronutrients can shape microbial activity and structure. Much information is available on the role of defined prebiotic fibers on gut microbiota, but less known are the effects of intact dietary fiber sources on healthy gut ecosystems. This research investigated in vitro the short-term effect of twenty-two commercially available food sources of dietary fiber on gut microbiota activity [pH, gas, short-chain fatty acids (SCFA), lactate] and specific composition of Firmicutes, Bacteroidetes, bifidobacteria and lactobacilli populations. More than 80% (19 of 22) of the products were highly fermentable and induced SCFAs production, with specific product differences. In general, all the whole grain cereals had a similar effect on gut microbiota modulation, inducing acetate and butyrate production and increasing bifidobacteria levels. Incorporating and comparing a large variety of products, including "non-conventional" fiber sources, like konjac, bamboo fiber or seeds fiber, about which there is little information, contributes to our knowledge on the modulatory activity of diverse food fiber sources on human gut microbiota, and therefore potential health promotion through dietary fiber diversification.